De la réflexivité du sujet aux enquêtes pratiques dans l’activité d’éducateurs spécialisés - Sylvie Mezzena; Kim Stroumza; Laurence Seferdjeli; Pascal Baumgartner (Activités)
Drawing on Ogien and Quere’s situated approach to French sociology of action, linked to Dewey’s pragmatist philosophy, our analysis of the activities of special educators combined with a broader literature on work analysis suggests that the reflexivity of professionals is insufficient to account for the construction and effectiveness of the intervention process. As defined by Schon’s reflexive practitioner model and its offshoots, it is a work of distancing, analyzing and formalizing their practice and as such feeds a negative and restricted conception of professionalism. Our research was conducted by a team in a shelter for adolescents from dysfunctional families, required by policy to develop a new mission of integration. Despite team meetings targeting the development of new rules, weekly seminars aimed at solving recent practical problems, informal exchanges between colleagues during the course of their work, pre-or post-activity interviews and self-analysis undertaken with professionals for research purposes, the activity continually escapes formalization. Drawing on an alternative model of professionalism based on a Deweyan notion of survey, our analysis of surveys of professional practice, both longitudinal and cross-sectional, shows that intervention requires know-how built in to the activity, even where so-called "basic" practices are concerned. It continually requires exploratory adjustments driven by the elements of the action. This suggests that the implementation of the mission does not depend on applicationist logic. This approach leads to a form of externalization of thought during the activity, defining practice as the place where knowledge is constructed without subordinating it to reflexivity as an intellectual process added to practice.